2015
DOI: 10.1016/j.neuropharm.2014.09.024
|View full text |Cite
|
Sign up to set email alerts
|

First-in-class thyrotropin-releasing hormone (TRH)-based compound binds to a pharmacologically distinct TRH receptor subtype in human brain and is effective in neurodegenerative models

Abstract: Hardiman, O., First-in-class thyrotropin-releasing hormone (TRH)-based compound binds to a pharmacologically distinct TRH receptor subtype in human brain and is effective in neurodegenerative models, Neuropharmacology (2014), doi: 10.1016/j.neuropharm.2014.09.024. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resultin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 72 publications
0
20
0
Order By: Relevance
“…They noted that these receptors are pharmacologically distinct from TRH receptors in human pituitary, thus providing the possibility of a new TRH receptor subtype. 25 It is possible that the inconsistent effects of administered TRH and its analogues in humans may have been caused by their rapid degradation of and poor blood-brain barrier penetration. 26 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They noted that these receptors are pharmacologically distinct from TRH receptors in human pituitary, thus providing the possibility of a new TRH receptor subtype. 25 It is possible that the inconsistent effects of administered TRH and its analogues in humans may have been caused by their rapid degradation of and poor blood-brain barrier penetration. 26 …”
Section: Resultsmentioning
confidence: 99%
“…It may be noted that earlier studies indicated the possibility that novel TRH receptors may mediate the CNS actions of TRH-like peptides, and it can be postulated that the CNS effects of the peptides reported herein may be mediated through such a novel TRH receptor subtype. 2325 …”
Section: Resultsmentioning
confidence: 99%
“…The regulatory mechanism, in mammals, is that stimulated hypothalamic secretes TRH and works on the pituitary, binding of TRH to TRHR on the surface of pituitary gland cells, to increase synthesis and the release of TSH [32,33]. The TSH acts on the thyroid by interacting with TSHR to promote the secretion of THs [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence for efficacy of this TRH analogue in the treatment of spinocerebellar ataxia and other neurodegenerative disorders [36,37]. A new TRH analogue with potential for oral delivery is in preclinical development targeting neurodegenerative conditions [38].…”
Section: Oral Peptides That Are Systemically Absorbedmentioning
confidence: 99%